TANTANGAN GURU DALAM MENYUSUN SOAL MATEMATIKA SMK BERBASIS HOTS DI MASA PANDEMI COVID 19 - Edy Nurfalah; Rita Yuliastuti; Ahmad Miftahuddin (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2021)
Research based on the independent learning program related to the application of HOTS questions is aimed at making students have the ability to think critically and think creatively. Based on data according to (1) the program for international student assessment (PISA) in 2012 it was 375, in 2015 it was 386, and in 2018 it was 379 for math problems. The low PISA is due to the difficulty of teachers in compiling math problems, especially HOTS-based so that math problems are difficult for some students to understand. This was confirmed by the results of observations, that during the COVID-19 pandemic learning was carried out online with limited media such as WhatsApp and Zoom, so that the application of HOTS questions was difficult, especially in their preparation. So, the author conducted a study aimed at knowing the level of difficulty of teachers in compiling HOTS-based math problems during the pandemic. Obtained the formulation of the problem, namely; 1) how is the level of teacher difficulty in compiling HOTS-based math problems during a pandemic?, 2) how is the level of understanding of teachers in compiling HOTS questions?, 3) how do teachers overcome difficulties in compiling HOTS questions?. Qualitative descriptive research method with data collection techniques of observation, questionnaires, and interviews. Furthermore, data analysis is data reduction, presentation, and verification as well as data validity testing, namely credibility, transferability, frontability, and confirmability testing. The results of the study were 1) the difficulty level of the teacher in compiling HOTS-based math problems during the pandemic was different based on the difficulty indicators, 2) the teacher understood the basics of making HOTS questions such as the HOTS question level C4-C6 but had difficulty implementing it, 3) the teacher's way of overcoming the difficulties, namely independent learning from the internet, discussions between teachers, providing stimulus questions that lead to the majors of vocational students, and evaluating the annual meeting for implementing schools.